KEBIJAKAN PENGELOLAAN GURU SEKOLAH DASAR: PERMASALAHAN DAN SOLUSI - Hafizin, Hafizin; Mukarromah, Aenullael; Bayu Aditama, Wiranda (JURNAL KAJIAN ISLAM MODERN, 2024)
This research aims to analyze policies and strategies that can improve the distribution and quality of teachers in Indonesia. A literature study approach was used to explore literature relevant to this topic, with a focus on teacher management policies, participatory models in teacher management, multigrade learning (PKR), and training programs in teacher distribution. Literature analysis reveals that teacher management policies need to pay attention to aspects of recruitment, placement, welfare and technology integration. The participatory model and PKR are effective solutions for optimizing limited human resources in areas with a shortage of teachers. In-service training programs are also important to improve teacher competency. Thus, holistic and strategic policy implementation is needed to improve the distribution and quality of teachers in Indonesia, especially in remote areas, in order to improve the overall quality of education.